Analisis Strategi Restorasi Lahan Terdegradasi sebagai upaya Mitigasi Penurunan Keanekaragaman Hayati - Bima Ahmad Fatahillah; Sulaiman Sulaiman; Islamul Hadi; Evy Aryanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Land degradation is one of the main factors causing the decline in global biodiversity, which impacts ecosystem stability and the sustainability of environmental functions. Land restoration is a strategic approach in achieving ecosystem recovery while supporting the targets of the Sustainable Development Goals (SDGs), especially Goal 15 (Life on Land). This study aims to examine the effectiveness of various land restoration strategies through soil conservation, revegetation, and strengthening environmental legal aspects based on a literature review. The method used is a systematic literature review with a comparative analysis of previous studies from 17 selected studies encompassing global case studies from Asia, Africa, and Europe. The results of the study indicate that soil conservation is effective in reducing erosion by more than 50% and increasing soil moisture retention, mixed revegetation can accelerate biodiversity recovery compared to monoculture, while legal aspects play a role as a determinant factor in the sustainability of restoration although its implementation still faces institutional challenges. The research synthesis confirms that successful land restoration requires an integrated ecosystem-based approach, active human intervention, and strong and adaptive policy support.